Using competency-based intergated approach for professional training of future biology teachers - Fursa, Inna; Bakhmat, Liudmyla (My University, 2019)
The article deals with defining competency-based integrated approach in professional education, which is aimed at improving existing pedagogical systems and stimulates integration activity of modern educational institutions. When accomplishing a single strategy of professional students training, the idea of integrating personal, social and action aspects plays an important role. It stimulates coordinating the contents of subjects (outer integration) and forming integral features of a future professional personality (inner integration).
Fursa I. Using competency-based intergated approach for professional training of future biology teachers / I. Fursa, L. Bakhmat // Теоретична і дидактична філологія : зб. наук. пр. - Переяслав-Хмельницький : Домбровська Я. М., 2019. – Вип. 29. - C. 4-10.
Keywords: компетентнісно-інтегративний підхід, професійна підготовка, майбутні учителі біології, внутрішня інтеграція, зовнішня інтеграція; competency-based integrated approach, professional training, future biology teachers, inner integration, outer integration; компетентностно-интегративный подход, профессиональная подготовка, будущие учителя биологии, внутренняя интеграция, внешняя интеграция